1985
DOI: 10.1093/jn/115.11.1403
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Dietary Protein Type on the B-Cell and T-Cell Immune Responses in Mice

Abstract: The effect of 20 g/100 g diet of lactalbumin (L), casein (C), soy (S) and wheat (W) protein on the immune responsiveness of C3H/HeN mice has been investigated by measuring the humoral immune response to the T cell-independent antigen, TNP-Ficoll. The humoral immune response of mice fed the L diet was found to be higher than that of mice fed the C, S and W diets. On the other hand, delayed-type hypersensitivity, and splenic cell mitogen responses to phytohemagglutinin and concanavalin A did not differ among mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…A further study (Wong & Watson, 1995) has provided additional evidence that dietary WPC can enhance antibody responses to systemically-administered antigen in mice, possibly via a mechanism of enhanced lymphocyte activation and cellular function Bounous & Kongshavn, 1985;Wong et al, 1996). Thus, the common paradigm appears to be that some WPCs can potentiate immune activity, in particular B cell production of antibodies in response to systemic immunization Wong & Watson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A further study (Wong & Watson, 1995) has provided additional evidence that dietary WPC can enhance antibody responses to systemically-administered antigen in mice, possibly via a mechanism of enhanced lymphocyte activation and cellular function Bounous & Kongshavn, 1985;Wong et al, 1996). Thus, the common paradigm appears to be that some WPCs can potentiate immune activity, in particular B cell production of antibodies in response to systemic immunization Wong & Watson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…By increasing ␣-lactalbumin, a major human milk whey protein, and decreasing the content of ␤-lactoglobulin, a major bovine whey protein, which is absent from human milk, it is possible to reduce the total protein content in a formula and achieve a plasma amino acid profile in FF infants more similar to that of BF infants (7). Besides having a well-balanced amino acid composition, ␣-lactalbumin has antimicrobial and also other biological effects (8,9). Caseinoglycomacropeptide (CGMP) is cleaved off from -casein by pepsin digestion in the stomach and has also been shown to have antimicrobial, immunomodulatory, and prebiotic effects (10 -13), including promoting growth of bifidobacteria (14).…”
mentioning
confidence: 99%
“…In 1985 Bounous and Kongshavn were among the first researchers to demonstrate an immunoenhancing effect of β-lactoglobulin [5]. They showed that the whey proteins (principally β-lactoglobulin and BSA) increase the number of antibody-forming cells in the spleen of mice immunized with trinitrophenylated ficoll.…”
mentioning
confidence: 99%